Women’s Advocacy for Social Change through Family Therapy - Navabinejad, Shokouh (Applied Family Therapy Journal (AFTJ), 2024)
In our special issue dedicated to Women Studies, I explore various dimensions of women’s experiences and contributions across multiple domains. One of the most transformative areas where women have made a significant impact is in the field of family therapy. This article explores "Women’s Advocacy for Social Change through Family Therapy" as a prime example of how feminist principles can drive both individual empowerment and broader societal transformation. The intersection of feminism and family therapy has made significant strides in advocating for women’s rights and promoting social change. By addressing gender inequality, empowering women, and fostering social justice, feminist-informed family therapy has become a powerful tool for transformation. As we celebrate the contributions of women in this field, it is crucial to continue supporting and advancing feminist principles in family therapy practice, research, and training. Through collective efforts and continued advocacy, feminist family therapy stands as a powerful force for social change.